2010
DOI: 10.3324/haematol.2009.021428
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed expression of the T-cell receptor/CD3 complex and associated signaling molecules in CD30+ T-cell lymphoproliferations

Abstract: ConclusionsSeverely altered expression of the T-cell receptor/CD3 complex, T-cell receptor-associated transcription factors and signal transduction molecules is a common characteristic of systemic and cutaneous CD30 + lymphoproliferations, although the clinical behavior of these entities is very different. Since peripheral T-cell lymphomas, not otherwise specified retain the full expression program required for functioning T-cell receptor signaling, the differential expression of a subset of these markers migh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 39 publications
3
36
1
1
Order By: Relevance
“…Marker loss is a common feature in NPM/ALK-induced ALCL. 25,26 Moreover, in a previous study, we also observed a downregulation of mature T-cell markers after immortalization of a mature T-cell clone. 27 To further exclude an immature T-cell contamination in our experimental setting, we transduced OT-I T cells with the immature T-cell proto-oncogene LMO2.…”
Section: Discussionmentioning
confidence: 98%
“…Marker loss is a common feature in NPM/ALK-induced ALCL. 25,26 Moreover, in a previous study, we also observed a downregulation of mature T-cell markers after immortalization of a mature T-cell clone. 27 To further exclude an immature T-cell contamination in our experimental setting, we transduced OT-I T cells with the immature T-cell proto-oncogene LMO2.…”
Section: Discussionmentioning
confidence: 98%
“…ALCL is a T-cell lymphoma that shows little or no expression of the T-cell receptor and its associated molecules, such as CD3. 26,30 Although the expression of membranous T-cell markers in ALCL is low or undetectable, expression of CD3, CD5 and CD8 was detectable in a subset of ALCL.…”
Section: Discussionmentioning
confidence: 99%
“…8 In this issue of the journal, Geissinger et al expand their previous work and report on the disturbed expression of the TCR/CD3 complex and associated signaling molecules in CD30 + T-cell lymphoproliferations. 9 The analysis was conducted by immunohistochemistry on a large series of tissues comprising 71 cases of systemic ALCL (33 ALKpositive and 38 ALK-negative) and 19 primary cutaneous CD30 + lymphoproliferative disorders (10 cases of primary cutaneous ALCL and 9 of lymphomatoid papulosis) in comparison to 20 cases of PTCL, NOS. They found random losses in various combinations of the TCRa/β and the four CD3 subunits (γ, δ, ε and ζ chains) in most cases of systemic and cutaneous CD30 + lymphoproliferative disorders, contrasting with the homogeneous expression in most cases of PTCL, NOS.…”
mentioning
confidence: 99%